PENGARUH PERSEPSI ETIS DAN FREKUENSI KOMUNIKASI PEER GROUP TERHADAP TINGKAT PENGGUNAAN CHAT GPT OLEH MAHASISWA SEBAGAI MEDIA PEMBELAJARAN DIGITAL DI ERA EDUCATION 4.0 - Andika Al Hakiem, Muhammad; Naryoso, Agus; Surayya Ulfa, Nurist (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The growth of information and communication technology has brought various innovations to the field of education, including its learning systems. The presence of Chat GPT can provide convenience and enhance efficiency in the learning process within the education system in the era of Education 4.0. However, there are potential challenges associated with its use, such as the possibility of plagiarism and academic dishonesty. Using quantitative research methods, this study provides empirical results regarding the influence of ethical perceptions and the frequency of peer group communication on the level of Chat GPT usage by students as a digital learning medium in the era of Education 4.0. The simple linear regression analysis technique employed in this study is conducted to test the influence between one independent variable and one dependent variable. The findings of this research explain student behavior in the use of Chat GPT for academic purposes as a digital learning medium through ethical perceptions and the frequency of peer group communication.